Availability and Accessibility of Digital Literacy and Its Influence on Democratic Attitudes among Secondary School Students in Gusau Educational Zone, Zamfara State - Sule Muhammad; Muhammad Nasa’i (Penerbit Hellow Pustaka, 2026)
influence on democratic attitudes among secondary school students in the Gusau Educational Zone, Zamfara State. The rapid growth of digital technologies has made digital literacy an essential skill for accessing information, evaluating online content, and participating responsibly in civic and democratic activities. However, disparities in digital infrastructure and access in many developing regions may limit students’ opportunities to develop these competencies. The study employed a descriptive survey research design. The population comprised 8,753 SS2 students from public secondary schools in Gusau and Tsafe Local Government Areas. A sample of 348 students was selected using a stratified random sampling technique. Data were collected using a structured questionnaire titled Availability and Accessibility of Digital Literacy and Democratic Attitudes Questionnaire (AADLDAQ). The instrument was validated by experts and achieved a reliability coefficient of 0.89 using Cronbach’s Alpha. Data were analyzed using one-sample t-test and simple linear regression at a 0.05 level of significance. The findings revealed that digital literacy resources are significantly available and accessible to students in the study area. The results also indicated that digital literacy has a positive and significant influence on students’ democratic attitudes and participation. The study concluded that improving digital literacy resources and access in schools can strengthen students’ civic awareness and democratic engagement